Product optimization in vinyl acetate monomer process using model predictive control - Aainaa Izyan, Nafsun (2008)
The needs for effective control performance in the face of highly process interactions have call for better plantwide process control system synthesis method. As a practical illustration, a vinyl acetate monomer plant was considered. The aim was to develop a suitable control model and then its performance was analyzed. This research underwent several stages. First, data was generated from the simulation of vinyl acetate monomer process. This studies was performed using MATLAB71. This was followed by analyses of dynamic response of the process. Transfer functions was developed using First Order Plus Time Delay (FOPTD) equation. These transfer function are then used in development of Model Predictive Control (MPC). Lastly, model testing of vinyl acetate monomer process is done and followed by tuning process. The optimum value of Prediction horizon (P) and Control horizon (M) is determined from the tuning process. The result lead to the conclusion that the Model Predictive Control is better than PI controller specifically in optimize the desired production of vinyl acetate.